HUBUNGAN PERILAKU DIET DENGAN TERJADINYA GEJALA GASTRITIS PADA REMAJA PUTRI DI PONPES AR-RAUDLATUL HASANAH MEDAN - nasution, subang aini (JURNAL HEALTH REPRODUCTIVE, 2016)
Diet is a behavior that arrange eating pattern which is often intended to lose weight or adjust the intake of certain nutrients. Unhealthy diet makes teenage girls apply improper behavior in achieving the ideal body shape and eating the wrong setting, thus it often causes gastritis.The purpose of this study was to determine the relationship between the behavior of young women with the symptoms of gastritis. This research used analytic survey research with cross sectional design with a total sample of 58 girls who were in the class XII of Aliyah Ponpes Ar-Raudlatul Harikusumo Medan. Sampling technique used was total sampling technique. The instrument used in this study was a questionnaire. The data were processed and analyzed by a frequency distribution table and then they were tested using chi square test.The results showed that there is a relationship between dietary knowledge of young women and the symptoms of gastritis where X² count (16.668) > X² table (5.99 and p value (0.000) < α (0.05), There is a relationship between the attitude and the occurrence of the symptoms of gastritis where X² count (12.304) > X² table (3,841) and p value (0.000) < α (0.05), there is a correlation between the occurrence of the symptoms of gastritis action where X² count (17.817) > X² table (3,841) and p value (0.000) <α (0.05).There is a significant relationship between  behavior (knowledge, attitudes, actions) teenagers’ diet and the symptoms of gastritis. It is expected that teenaged girls keep trying to improve behavior of eating well and choose the right diet method so as not to cause the symptoms of gastritis.